Narzędzia zarządzania na tle współczesnych tendencji biznesowych - Skrzypek, Piotr (Management Tools Against a Background of Current Business Tendencies, 2006)
Everyone says that the business conditions have been changing constantly. Moreover, going further, it is possible to indicate that such process influences the management style meaningfully. Every solution, according to its creators, allows to support the company in certain area. However, in business reality not every tool provides promised solutions. This article present the general overview of business tendencies and related management tools. It brings also information about the frequency of usage of such items and gives general scope on level of satisfaction of the users.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 144-152